Program Literasi Sekolah: Dampak terhadap Prestasi Belajar dan Karakter Siswa di Sekolah Dasar Islam - Khasanah, Dyka Uswatun; Afandi, Muhamad; Sari, Yunita (Diniyah: Jurnal Pendidikan Dasar, 2025)
The School Literacy Movement is a strategic initiative to enhance the reading and writing culture among elementary school students. This qualitative study aims to analyze the implementation and benefits of the literacy program at SD Islam Sultan Agung 2 Semarang in developing students' literacy skills, character, and creativity. Data were collected through interviews, observations, and documentation involving the school principal and teachers. Data analysis was conducted using triangulation techniques, including data reduction, presentation, and verification. The findings reveal that the literacy program is implemented through various activities such as classroom reading corners, literacy wall magazines, morning Qur’an recitation, writing competitions, and storytelling events. These practices have been proven to enhance students' academic performance, particularly their reading comprehension and text analysis skills. Additionally, literacy activities contribute to the development of critical thinking, communication, and character values such as responsibility and empathy. The challenges identified include limited reading materials, inadequate library facilities, and minimal parental involvement. This study concludes that the School Literacy Movement plays a significant role in shaping literate and character-driven student profiles. The implications of this research highlight the need to strengthen collaboration among schools, teachers, parents, and policymakers to ensure the sustainability of foundational literacy programs in elementary education.Keywords: School literacy movement, academic achievement, character development, reading culture